Particle precipitation : effects on selected ionospheric phenomena - Lunde, June (Universitetet i Tromsø, 2009)
Papers 2 and 4 are not available in Munin: 2. T. Grydeland, B. Gustavsson, L. Baddeley, J. Lunde, and E. M. Blixt: 'Conditional integration of Incoherent Scattering in relation to flickering aurora', Journal of Geophysical Research (2008), vol.113, A08305, 8pp. Available at http://dx.doi.org/doi:10.1029/2008JA013039 4. B. Gustavsson, J. Lunde, and E. M. Blixt: 'Optical observations of flickering aurora and its spatio-temporal characteristics', Journal of Geophysical Research (2008), vol.113, A12317, 8pp. Available at http://dx.doi.org/10.1029/2008JA013515 The motivation behind this thesis has been to study particle precipitation from the Sun into the Earth’s upper atmosphere and its effects on selected ionospheric phenomena. Particles from the solar wind can enter the Earth's magnetosphere through magnetic merging, either at the sub-solar point, or at higher latitudes, depending on the configuration of the interplanetary magnetic field. This interaction can be studied from the ground at Svalbard, due to its fortuitous location beneath the magnetospheric cusp region on the dayside, and its location inside the polar cap during night-time. It has been studied how these precipitating particles act on the aurora and ion-acoustic waves in the ionized part of the atmosphere. The studies have been conducted using various methods, including extracting data from databases, running different experiments and building new instrumentation. The latter was a radiation detector for measuring Bremsstrahlung X-rays. The main instrument used for this study has been the EISCAT (European Incoherent SCATtering) radar located at Svalbard, together with an assortment of other ground based instruments such as photometers, riometers and magnetometers. In addition, particle instruments onboard satellites have been used as well as an X-ray instrument mounted on a balloon launched from Longyearbyen. Primarily, it is the effect of particle precipitation on large ion-acoustic waves that has been studied. These waves can be observed by ...